Therapist use of cognitive behavior therapy and eye movement desensitization and reprocessing components for the treatment of posttraumatic stress disorder in practice settings - Neill, Erin L.; Zarling, Amie; Weems, Carl F. (Frontiers in Psychology, 2023)
Introduction Treatment practice guidelines for posttraumatic stress disorder (PTSD) recommend both Eye Movement Desensitization and Reprocessing (EMDR) and Cognitive Behavior Therapy (CBT); however, implementation in practice setting remains challenging. Here we aim to foster implementation efforts for PTSD by identifying the relative use of the various components of empirically supported treatments by therapists and the characteristics that predict their use. Methods Surveyed 346 therapists (84.07% female) of whom 272 participants (78.61%) were trained primarily in CBT and 135 participants (39.02%) were trained in primarily in EMDR. Assessed relative use of various EMDR and CBT components as well as several training and personality factors. Results Psychoeducation about trauma was the most common element used. “Off label” use of components was also identified with application of EMDR techniques to other diagnoses. Findings also suggest underutilization of in vivo exposure techniques across therapists. EMDR therapists reported relatively high use of core EMDR techniques (i.e., greater use of EMDR core techniques). Big five personality factors, therapy efficacy, and anxiety were associated with differential component use. Discussion Results identify trends in empirically supported component use and therapist characteristics that are associated with the use of various techniques for PTSD. The findings suggest implementation efforts could foster training in underused techniques, address barriers to their utilization and develop knowledge of effective packages of components.